The Problem of Integrity of the Integral Democracy Project - Peluritis, Laurynas (Politologija, 2021)
The topic of this paper is the most important principles of the concept of integral democracy created by Stasys Šalkauskis, Antanas Maceina and other Lithuanian interwar and post-war exodus intellectuals. The genesis and development of the ideas of integral democracy in interwar Lithuania are analyzed, also the influence of the experiences of World War II, occupations, totalitarian regimes and living in exodus on this concept. The projects of integral democracy, organic state and non-worldview politics are reviewed in their historical and intellectual context of Lithuania and the Lithuanian diaspora in exodus, starting from the origins of the idea and the concept of the organic state, also the most important criticism of it. The second part of the paper reviews the most important assumptions and ideas that unite the whole project from the 1936 concept of the organic state to the 1954–1955 ideas of integral democracy. Finally, looking at the fundamental differences between the two concepts the essence and key features of the project of full democracy are highlighted.